The effects of the Pilates method in individuals after stroke: a systematic review with meta-analysis - Kiefer, Kênia; Alvim Scianni, Aline; Guimarães da Silva, Lívia Carolina; Avelino, Patrick Roberto; Coelho de Morais Faria, Christina Danielli (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Pilates has shown significant effects in post-cerebrovascular accident (CVA) patients. Objective: To carry out a systematic review with meta-analysis, investigating the effects of the Pilates method in post-stroke individuals. Methods: An electronic search was performed using an optimized strategy in the Medline, CINAHL, SPORTDiscus, Web of Science, LILACS and PEDro databases, plus a manual search. Clinical trials that used the Pilates method in post-stroke rehabilitation, in functionality outcomes, were included. Studies were reviewed by two independent reviewers. Methodological quality was assessed using the PEDro scale. Results: Seven studies were included. The results of the meta-analyses showed that Pilates was effective in improving mobility (-3 seconds; CI 95% -4 to -1; p=0.009), assessed by the Timed Up and Go, and quality of life (SMD 1 .1; 95% CI 0.5 to 1.58; p<0.001) of individuals after stroke. Regarding the descriptive results, Pilates proved to be effective in improving lower limb motor function, cardiopulmonary function, step length, and gait ability. Conclusion: This systematic review showed, through meta-analysis, that the Pilates method is effective in improving the mobility and quality of life of post-stroke individuals. In addition, descriptive results were significant for lower limb motor function, cardiopulmonary function, step length, and gait ability. However, these latter results deserve caution, as they were all based on descriptive results from only one clinical trial each.